A MODEL AND RESEARCH AGENDA FOR LEASE DECISION MAKING - Neelam Goela; Jayne E. Bisman (Universitas Trisakti, 2013)
Internationally, the accounting and finance literature provides a basis for identifying a range of rationales used in lease decision-making, and a number of accounting and financial factors purported to influence the lease versus borrow and buy decision, particularly with respect to finance leases, has been identified. In this paper the lease versus borrow and buy decision is characterised as multidimensional and multi-factorial. A simple trend analysis of archival, statistical data of leasing in Australia over sixteen financial years (1985-86 to 2000-01) is presented to form a basis for examining and discussing these factors within the context of the international literature on leasing. The trend analysis and literature review provided evidence to suggest that much of the conventional, theoretical wisdom concerning the factors important in lease versus borrow and buy decisions may be overemphasised, particularly that related to the influence of accounting treatments and the impact of tax regimes on leasing. Based on the review we develop and describe a constituted, multi-dimensional model of lease decision-making and offer suggestions for the development of improved lease or purchase decision frameworks and for further research in the area that will be more capable of handling this multi-dimensionality. Application of this knowledge will advance the research agenda, improve the decisions of lessees, benefit lessors who provide lease finance, and direct accounting policy makers.